An evaluation of peptone products and fish meal on nursery pig performance - Myers, A.J.; Moline, J.; Xu, G.; Ratliff, B.W.; McKilligan, D.M.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 360 nursery pigs (PIC C327 × 1050, initially 11.8 lb and 21 d of age) were used in a 35-d study to evaluate the effects of select menhaden fish meal (SMFM), PEP2+ (also known as Ferm O Tide), Peptone 50, and PEP-NS on nursery pig performance. PEP2+, Peptone 50, and PEP-NS are all porcine intestinal mucosa products, but differ based on the carriers with which they are co-dried. PEP2+ is co-dried with enzymatically processed vegetable proteins. Peptone 50 is co-dried with a vegetable protein, while PEP-NS uses by-products from corn wet-milling. Phase 1 diets were fed in pellet form from d 0 to 8. Phase 2 diets were fed in meal form from d 8 to 21. A common corn-soybean meal diet was fed from d 21 to 35. There were 6 dietary treatments: (1) a negative control diet containing 2.5% spray-dried animal plasma (SDAP) in Phase 1 followed by no specialty protein sources in Phase 2; (2) a diet containing 5% SDAP in Phase 1 and 3% SMFM in Phase 2; (3) a blend of 5% SDAP and 3% SMFM during Phase 1 and 6% SMFM during Phase 2; (4) a blend of 5% SDAP and 3% PEP2+ during Phase 1 and 6% PEP2 during Phase 2; (5) a blend of 5% SDAP and 3% PEP 50 during Phase 1 and 6% PEP50 during Phase 2, and (6) a blend of 5% SDAP and 3% PEP-NS during Phase 1 and 6% PEP-NS during Phase 2. During Phase 1, there were no differences in F/G among pigs fed any of the dietary treatments. During Phase 2 (d 8 to 21), pigs fed 6% PEP2+ had greater (P < 0.05) ADG compared to those fed the negative control diet, 3% or 6% fish meal, with pigs fed PEP50 and PEP NS intermediate. Furthermore, pigs fed 6% PEP2+ had the greatest improvement (P < 0.02) in F/G compared to pigs fed all other experimental diets. Overall, pigs fed diets containing PEP2+ had increased (P < 0.03) ADG and ADFI compared to pigs fed the negative control diet. Pigs fed 3% PEP2+ during Phase 1 and 6% PEP2+ during Phase 2 had greater (P < 0.05) ADFI compared to those fed 3% SMFM during Phase 1 and 6% SMFM during Phase 2. In conclusion, PEP2+, Peptone 50, and PEP-NS can be used as specialty protein sources to replace select menhaden fish meal in Phase 2 nursery pig diets. In addition pigs fed PEP2+ had greater ADG than those fed fish meal.
Keywords: Swine; Fish meal; PEP2+; Peptone 50; PEP-NS; Spray-dried animal plasma